Poorly soluble cobalt oxide particles trigger genotoxicity via multiple pathways. Issue 1 (December 2015) - Uboldi, Chiara; Orsière, Thierry; Darolles, Carine; Aloin, Valérie; Tassistro, Virginie; George, Isabelle; Malard, Véronique
Abstract Background Poorly soluble cobalt (II, III) oxide particles (Co3 O4 P) are believed to induce in vitro cytotoxic effects via a Trojan-horse mechanism. Once internalized into lysosomal and acidic intracellular compartments, Co3 O4 P slowly release a low amount of cobalt ions (Co2+ ) that impair the viability of in vitro cultures. In this study, we focused on the genotoxic potential of Co3 O4 P by performing a comprehensive investigation of the DNA damage exerted in BEAS-2B human bronchial epithelial cells. Results Our results demonstrate that poorly soluble Co3 O4 P enhanced the formation of micronuclei in binucleated cells. Moreover, by comet assay we showed that Co3 O4 P induced primary and oxidative DNA damage, and by scoring the formation of γ-H2Ax foci, we demonstrated that Co3 O4 P also generated double DNA strand breaks. Conclusions By comparing the effects exerted by poorly soluble Co3 O4 P with those obtained in the presence of soluble cobalt chloride (CoCl2 ), we demonstrated that the genotoxic effects of Co3 O4 P are not simply due to the released Co2+ but are induced by the particles themselves, as genotoxicity is observed at very low Co3 O4 P concentrations.